Coalition of Oct4A and β1 integrins in facilitating metastasis in ovarian cancer. Issue 1 (December 2016) - Samardzija, Chantel; Luwor, Rodney; Quinn, Michael; Kannourakis, George; Findlay, Jock; Ahmed, Nuzhat
Abstract Background Ovarian cancer is a metastatic disease and one of the leading causes of gynaecology malignancy-related deaths in women. Cancer stem cells (CSCs) are key contributors of cancer metastasis and relapse. Integrins are a family of cell surface receptors which allow interactions between cells and their surrounding microenvironment and play a fundamental role in promoting metastasis. This study investigates the molecular mechanism which associates CSCs and integrins in ovarian cancer metastasis. Methods The expression of Oct4A in high-grade serous ovarian tumors and normal ovaries was determined by immunofluorescence analysis. The functional role of Oct4A was evaluated by generating stable knockdown (KD) of Oct4A clones in an established ovarian cancer cell line HEY using shRNA-mediated silencing. The expression of integrins in cell lines was evaluated by flow cytometry. Spheroid forming ability, adhesion and the activities of matrix metalloproteinases 9/2 (MMP-9/2) was measured by in vitro functional assays and gelatin zymography. These observations were further validated in in vivo mouse models using Balb/c nu/nu mice. Results We report significantly elevated expression of Oct4A in high-grade serous ovarian tumors compared to normal ovarian tissues. The expression of Oct4A in ovarian cancer cell lines correlated with their CSC-related sphere forming abilities. The suppression of Oct4A in HEY cells resulted in a significant diminution of integrin β1 expression and associated α5 and α2 subunits compared to vector control cells. This was associated with a reduced adhesive ability on collagen and fibronectin and decreased secretion of pro-MMP2 in Oct4A KD cells compared to vector control cells. In vivo, Oct4A knock down (KD) cells produced tumors which were significantly smaller in size and weight compared to tumors derived from vector control cells. Immunohistochemical analyses of Oct4A KD tumor xenografts demonstrated a significant loss of cytokeratin 7 (CK7), Glut-1 as well as CD34 and CD31 compared to vector control cell-derived xenografts. Conclusion The expression of Oct4A may be crucial to promote and sustain integrin-mediated extracellular matrix (ECM) remodeling requisite for tumor metastasis in ovarian cancer patients.